Application of the quality control methodologies to a novel solid dosage co-crystal model system - Alkhalil, Aalae (2013)
Co-crystals are multi-component, single phase materials in which the co-crystal formers exist in an uncharged state. This interaction between components occurs without affecting the intra-molecular covalent bonding of the involved components or altering their chemical integrity. This class of materials has recently gained the interest in the pharmaceutical industry for modifying the physico-chemical properties of some active pharmaceutical ingredients (APIs) such as solubility, hygroscopicity, and mechanical properties.